The impact of using concept maps in learning the skill of preparing volleyball players - Hakit, Ali (Journal of Physical Education, 2017)
The maps concepts are tool enable us to organization concedes in hierarchical format ranging in which the concepts by degree abstraction from its the most abstract to concepts least abstraction thus stand out the relations between the concepts is increasing the link and meaning among themselves, the problem find it is through the work of the researcher as an assistant coach team volleyball in directorate rusafa second noted twice a clear relation to understand application. Skills volleyball demolition of their knowledge with its laws of lissome players the objective of search to the construction of education program in accordance with the strategy of maps concepts players squad raising rusafa second in Baghdad ball plane. have chosen the researcher curriculum pilots convenient to search the sample is made up than30 player distributors event the researcher concluded that learning at the skill of preparation at the end of the learning period and the researcher recommended that the attention of volleyball coach to use the strategy of conceptual maps in the development of learning processes in the two sides of the application and theoretical.